Reclaiming sociological reduction: Analysing the circulation of management education in the periphery. Issue 5 (November 2017) - Alcadipani, Rafael
Management knowledge and practices have been circulating worldwide for a long time, and business and management schools are central locations where management knowledge and practices have been produced. Few studies discuss how this circulation occurs in the periphery in general and how management education from the United States has circulated in the periphery in particular. Using historical research, this article aims to reclaim the notion of sociological reduction, a notion developed by Brazilian scholar in the 1950s, to make sense of how US management education was implemented in a Brazilian management school. By doing so, this article contributes to the analysis of the spread of US management education grounded in a postcolonial approach and addresses calls for analysing epistemologies from the periphery.